Metabolomic Profiling, Antioxidant and Enzyme Inhibition Properties and Molecular Docking Analysis of Antarctic Lichens - Alfredo Torres-Benítez; José Erick Ortega-Valencia; Marta Sanchez; Pradeep Kumar Divakar; Mario J. Simirgiotis; María Pilar Gómez-Serranillos (Molecules, 2022)
The lichen species Lecania brialmontii, Pseudephebe pubescens, and Sphaerophorus globosus are part of the prominent lichenoflora of the Antarctic territory. In this work, we report the metabolomic identification of ethanolic extracts of these species, their antioxidant and cholinesterase enzyme inhibitory activity, and conduct a molecular docking analysis with typical compounds. Eighteen compounds were identified by UHPLC-ESI-QTOF-MS in L. brialmontii, 18 compounds in P. pubescens, and 14 compounds in S. globosus. The content of phenolic compounds was variable among the species, ranging from 0.279 to 2.821 mg AG/g, and all three species showed high inhibition potential on the cholinesterase enzymes. Molecular docking showed important interactions between AChE and BChE with the selected compounds. This study evidences the chemical fingerprint of three species of the order Lecanorales that support the continuation of the study of other biological activities and their potential for medical research.